Critical thinking skills among nurses at a private hospital in Penang: a quantitative study / Nordianna Seman and Yeap Wei Lin - Seman, Nordianna; Yeap, Wei Lin (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
Nurses face a great challenge in making significant and crucial decisions that will impact the outcome of patients' overall health status. Therefore, critical thinking skills are crucial for nurses to make the sound clinical decisions to assure the provision of high- quality nursing care. Thus, this study is aimed to provide the current evidence of the critical thinking level of registered nurses and identify the factors that affect critical thinking skills among the nurses. The quantitative study design with a cross-sectional survey was implemented in this study. Registered nurses from various clinical backgrounds at a private hospital in Penang were selected by using the stratified random sampling (N=169). Watson-Glaser Critical Thinking Appraisal (WGCTA) questionnaire was adopted to measure the critical thinking abilities among the participants. An average level of critical thinking skills was found in this study. The senior nurses scored lower on the critical thinking scale compared to the junior nurses. Besides, there is a relationship between the nurses' educational level and critical thinking abilities. This study concludes that there is a difference in critical thinking abilities among the nurses. Therefore, future research is suggested to further investigate this issue as this skill of thinking leaves a profound impact on the patients' outcome.